Proceedings of the International Conference on Recent Cognizance in Wireless Communication & Image Processing ICRCWIP-2014 - Afzalpulkar, Nitin; Srivastava, Vishnu; Singh, Ghanshyam; Bhatnagar, Deepak; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2016)
This volume comprises the proceedings of the International Conference on Recent Cognizance in Wireless Communication & Image Processing. It brings together content from academicians, researchers, and industry experts in areas of Wireless Communication and Image Processing. The volume provides a snapshot of current progress in computational creativity and a glimpse of future possibilities. The proceedings include two kinds of paper submissions: (i) regular papers addressing foundation issues, describing original research on creative systems development and modeling; and (ii) position papers describing work-in-progress or research directions for computational creativity. This work will be useful to professionals and researchers working in the core areas of wireless communications and image processing.
Broadband Modified U Shaped Patch Antenna for Wireless Communication -- Performance Improvement of Epidemic Routing Protocol of Delay tolerant Networks By using Improved Buffer Management -- Elliptically Slotted Self Affine 8-Shaped Fractal Multiband Antenna -- Design of Compact Triangular Patch Antenna for WIMAX Applications -- Post Accident Assistance using on Board Diagnostics and Smart Phones -- Digital Image Forensics and Counter Anti-Forensics -- Can We Use Mass Based Similarity Measure in Classification? -- CNT Based Biomedical Sensor for Cancer Detection -- Effective Role of Thrashing in Load Balancing During VM Live Migration -- Real Time Abandoned Object Detection using Video Surveillance -- Request allocation and Resource Management Techniques in Cloud Computing -- Blind Image Watermarking of Variable Block Size for Copyright Protection -- Compact Goblet Shaped Single Band Notched UWB Antenna -- An Application of Firefly Algorithm for Clustering in Wireless Sensor Networks -- Microstrip Antenna with Defected Ground Structure (DGS) for Multiband Operation -- Design of a Compact Novel Planar Dual Band-Notched UWB Antenna -- X-Band and Ku-Band Patch antenna for Radiolocation Applications -- Procuring Wireless Sensor Actuator Network Security -- Performance analysis of Voip Over Wimax Networks under Nodes Failure -- Design of Reduced Order Controller for Mechanical System -- A Survey on Black-Hole attack in Manet -- Area Efficient FPGA Model of LMS Filtering Algorithm. An Efficient Hybrid- Cascaded Framework for Emission Computed tomography using Osem Image Reconstruction Algorithm -- A Review of Energy Efficient Routing Protocols in Wireless Sensor Networks -- A Study of Phase Shifting Surface -- Review on Student attendance Maintenance System: A Discontentment.
Keywords: Telecommunication; Signal processing; Pattern recognition systems; Communications Engineering, Networks; Signal, Speech and Image Processing .; Automated Pattern Recognition